Genetic Susceptibility and Mechanisms for Refractive Error - Stambolian, Dwight (2013)
Refractive errors, myopia and hyperopia, are the most common causes of visual impairment worldwide. Recent advances in genetics have been utilized to identify a wealth of genetic loci believed to contain susceptibility genes for refractive error. The current genetic evidence confirms that refractive error is influenced by both common and rare variants with a significant environmental component. These studies argue that only by combining genetic knowledge with in vivo measurements of biological states will it be possible to understand the underlying biology of refractive error that will lead to novel therapeutic targets and accurate genetic predictions.